2018
DOI: 10.1021/acsenergylett.8b00475
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Enhanced Photoluminescence Quantum Yield in MAPbBr3 Perovskite with Reduced Crystal Size

Abstract: Methylammonium lead bromide perovskite (MAPbBr3) has been widely investigated for applications in visible perovskite light-emitting diodes (LEDs). Fine-tuning of the morphology and of the crystal size, from the microscale down to the quantum confinement regime, has been used to increase the photoluminescence quantum yield (PLQY). However, the physical processes underlying the PL emission of this perovskite remain unclear. Here, we elucidate the origin of the PL emission of polycrystalline MAPbBr3 thin films by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
129
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 76 publications
14
129
0
Order By: Relevance
“…The microcavity quality factor was found to be around 92 and the measured Rabi splitting Ω Rabi was 70 meV. Firstly, our observation of the strong coupling regime is coherent with a dominant excitonic regime in CH 3 NH 3 PbBr 3 at room temperature, in good agreement with the most recent paper about this topic [49]. Secondly, this result is particularly important because it indicates that it is possible to obtain the strong coupling regime in solution-processed films of 3D perovskite.…”
supporting
confidence: 91%
“…The microcavity quality factor was found to be around 92 and the measured Rabi splitting Ω Rabi was 70 meV. Firstly, our observation of the strong coupling regime is coherent with a dominant excitonic regime in CH 3 NH 3 PbBr 3 at room temperature, in good agreement with the most recent paper about this topic [49]. Secondly, this result is particularly important because it indicates that it is possible to obtain the strong coupling regime in solution-processed films of 3D perovskite.…”
supporting
confidence: 91%
“…The nanostructured MAPbBr 3 film showed a higher PL quantum yield (PLQY, 27%) than the pure MAPbBr 3 film (0.1%), as shown in Figure c. The improved PLQY is attributed to favored excitonic recombination by reducing crystal size together with reduced surface trapping resulting from efficient passivation by the additives …”
Section: Resultsmentioning
confidence: 99%
“…As has been shown by Zheng et al, a significantly higher E b is found in MAPbBr 3 nanoparticles compared to bulk MAPbBr 3 , leading to the increased photoluminescence quantum yield (PLQY) seen in perovskite structures with reduced dimensionality . In a recent study by Droseros et al, the physical processes that govern the PL emission of polycrystalline MAPbBr 3 films and films containing smaller crystal sizes were explored . They also found enhanced PLQY for crystals with smaller size due to higher excitonic recombination and surface passivation.…”
Section: Photoluminescence Propertiesmentioning
confidence: 90%
“…Liu et al [33] Temperature-dependent PL Thin film with crystallites of 100s nm to a few µm size 25.9 meV Droseros et al [28] Excitation density-dependent integrated PL Polycrystalline thin film 110 meV…”
Section: Polycrystalline Thin Film 17 Mevmentioning
confidence: 99%